Advocates’ Perception of the Secondary Victimization of Rape Survivors by Law Enforcement, the Legal System, and Hospital Professionals - Maier, Shana L. (Violence against women, 2025)
Sexual victimization occurs frequently and it remains important to consider rape victim advocates’ perceptions of survivors' secondary victimization due to treatment from police, the legal system, and medical professionals working in hospital emergency departments. Data from interviews with 41 U.S. advocates provide a comprehensive perspective of secondary victimization. Most advocates perceive that survivors face secondary victimization because they are doubted or blamed, face repeated questioning, feel left out of the legal processes, experience invasive evidence collection, and do not receive the desired legal outcome. Advocates share their ways to reduce secondary victimization, such as preparing, empowering, and listening to survivors.